Analysis of Signs and Symptoms of Premenstrual Syndrome with Postpartum Blues Occurrence in Postpartum Mothers on the Seventh Day at Pmb Lailatul Mariam, A.Md.Keb, Pasuruan Regency - Wahyuni, Candra; Nita Dwi Astikasari; Kyky Yunita Sari Suharto (Universitas STRADA Indonesia, 2016)
Postpartum bluesis something that needs to be considered, because it is a mental disorder (affective) that occurs in women after giving birth. Postpartum blues is a period of emotional stress that occurs in 80% of mothers after giving birth. Social problems, environment, family relationships, and medical history such as premenstrual syndrome (PMS) can be predisposing factors for postpartum blues. Support from midwives is needed so that it can be addressed immediately if the mother feels symptoms of postpartum blues. The purpose of this study was to analyze the signs and symptoms of premenstrual syndrome with the incidence of postpartum blues in postpartum mothers on the seventh day at PMB Lailatul Mariam, A.Md.Keb. This type of research uses a cross-sectional analytical method. The number of samples was 35 people with accidental sampling. The statistical test used was the Fisher's Exact Test. The results of this study were that most postpartum mothers experienced premenstrual syndrome and postpartum blues, namely17 respondents (48.6%). The results of the study mshowed no significant signs and symptoms of premenstrual syndrome with the occurrence of postpartum blues in postpartum mothers on the seventh day becausethe p-value > ɑ (0.451> 0.05). The conclusion of this study is that there is no relationship between signs and symptoms of premenstrualsyndrome with the occurrence of postpartum blues in postpartum mothers on the seventh day at PMB Lailatul Mariam, A.Md.Keb.